Successful change management from strategy to transformation: results of an EC project. (1st January 2002) - Schuh, Guenther; Mueller, Mathias; Tockenbuerger, Lueder W.; Tanner, Hans R.
Change projects seldom end with success when special or chosen employees such as expert rounds or lead staff create strategies, concepts and plans for their implementation while the rest of the employees are treated like chess figures. The change management concept MOTION, which results from an EC project, is based on these recognitions - the team oriented participative analysis and construction of the enterprise processes - and creates transparency of the overlapping process functions for the participants from strategy to transformation.